Pengaruh Perubahan Harga Emas, Harga Minyak Dunia, Tingkat Suku Bunga BI, dan Nilai Tukar Terhadap Return Saham Pada Indeks Harga Saham Gabungan (IHSG) dan Jakarta Islamic Index (JII) - Ardilla Putri Naina Sari; Robiyanto Robiyanto; Budi Frensidy (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
This study examines the effect of the USD/IDR exchange rate, BI rate, gold price, and oil price on the return of the Jakarta Composite Index (JCI) and Jakarta Islamic Index (JII) from 2015-2021. The data used in this study is secondary data, data obtained from the monthly closing price of each variable sourced from the IDX website, yahoo finance, the official website of the Indonesian Central Bank, www.lbma.org.uk, www.eia.gov. Sampling was carried out using purposive sampling technique with the number of samples obtained was the closing price of 84 months. The analytical technique used in this study is multiple regression analysis with the Ordinary Least Square (OLS) method. The results obtained in this study indicate that BI rate and the USD/IDR exchange rate have a negative effect on the return of the JCI and JII. Gold prices have a negative effect on the JCI, while the JII has a positive effect. And the oil price variable shows a positive effect on JCI, and negative on JII.